Nursing organizations in Western Europe from the 16th to 18th centuries - Supady, Jerzy (Health Promotion & Physical Activity, 2019)
From the 16th to 18th centuries in Western Europe care and nursing institutions for the sick were created by the faithful of the Catholic Church. The greatest successes in that field were achieved by three persons: Juan de Dios, Camillo de Lellis and Vincent de Paul. They established charity, care and nursing congregations, orders and convents which conducted wide charity activities in Europe before the French Revolution.